Composite abrasive nickel-phosphorus grating microstructure shape-preserving polishing method
Through the combination of composite abrasives and polishing pads of different hardness, the problem of removing residual knife marks and retaining shape in nickel phosphorescent grating microstructure polishing is solved, achieving low-cost and efficient polishing, suitable for various surface types and large sizes Workpieces meet high imaging quality requirements.
Patent Information
- Application Number
- CN202411459890.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-10
AI Technical Summary
The existing polishing technology is difficult to effectively remove residual cutter marks and reduce surface roughness while maintaining the shape of the nickel phosphor grating microstructure, especially in optical systems that meet high imaging quality requirements, and the existing methods are costly or inefficient. , and there are limitations on the size of the workpiece.
The nickel phosphorescent grating microstructure conformal polishing method adopts composite abrasives. Through the combination of abrasives of different hardness and polishing pads, the residual knife marks with higher hardness are removed with higher undulations, and then the high frequency is removed with lower hardness abrasives. Error, combined with compression deformation and rotational motion, realizes the removal of medium and high frequency errors and takes into account the grating shape.
It realizes the removal of residual knife marks and reduces surface roughness without destroying the shape of the microstructure. It is suitable for various surface types and large-size workpieces, with low cost and no vacuum or magnetic field conditions required, and is suitable for large-scale industrial production.
Smart Images

Figure CN119282827A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polishing method, in particular to a conformal polishing method for a nickel-phosphorus grating microstructure using a composite abrasive. Background Art
[0002] Chemically plated nickel-phosphorus alloy has good properties such as uniformity, density, good machinability, good polishability, high hardness, good corrosion resistance, and good wear resistance, and is an excellent reflector modification material. At present, the nickel-phosphorus alloy modification layer is usually plated on the aluminum alloy reflector, which can improve the surface defects and achieve a very low surface roughness through polishing. It has been widely used in optics, military industry, aerospace and other fields, and has extremely high application value.
[0003] Based on the good machinability of nickel-phosphorus alloy coating, various optical microstructures can be processed by single-point diamond turning process to meet various optical usage requirements, such as grating microstructure. Grating is an important optical microstructure that can effectively screen light of different wavelengths and is widely used in optical reflectors. The surface of nickel-phosphorus alloy after turning can meet the imaging requirements of general infrared systems, but due to the forming mechanism of turning, spiral cutting marks will remain on the surface of nickel-phosphorus alloy after processing. These marks will lead to an increase in diffraction effect and stray light, increase light flux loss, reduce reflectivity and image quality, and cannot meet the requirements of optical systems with short wavelengths and higher imaging quality. Polishing is required to remove them. In order to meet higher usage requirements, the surface of nickel-phosphorus grating microstructure after single-point diamond turning is optically polished. While improving the surface quality and removing residual marks, the shape of the grating microstructure must also be taken into account. The necessary condition is that the medium frequency roughness (MSFR, spatial period 1mm~1μm) RMS <1nm. Therefore, conformal polishing on the surface of nickel-phosphorus grating microstructure is still a challenging problem.
[0004] At present, there are many polishing technologies used to remove residual tool marks after turning nickel-phosphorus alloys, such as magnetorheological polishing, ion beam polishing and chemical mechanical polishing. Magnetorheological polishing is a polishing method in which a polishing wheel drives a controllable magnetic fluid to remove optical surface materials under specific magnetic field conditions. Ion beam polishing is a polishing method that uses high-energy ions to bombard the workpiece under a vacuum state to achieve material removal. Chemical mechanical polishing is a method of polishing by mechanical removal of abrasives and chemical corrosion of oxidants to remove surface materials of the workpiece.
[0005] Magnetorheological polishing has a stable removal function and high polishing efficiency. However, magnetorheological polishing causes great damage to the microstructure shape, has poor conformal ability, and is prone to periodic traces of polishing. It has insufficient ability to improve surface quality and limited smoothing ability. Ion beam polishing can achieve precise material removal at the atomic level without introducing any external contamination, and has excellent conformal ability. However, ion beam polishing machines are expensive and need to be carried out in a vacuum environment. The polishing rate is low, and the vacuum chamber has certain restrictions on the polishing size of the workpiece. Chemical mechanical polishing is a surface polishing method that combines chemical modification and abrasive removal. It has good conformal ability, can achieve global flattening, has low cost, and has moderate polishing efficiency. Therefore, it is widely used in the industry and is an important polishing technology for the industrial and large-scale production of nickel-phosphorus mirrors.
[0006] For chemical mechanical polishing, as the industry's requirements for polishing efficiency and surface quality continue to increase, in many cases, it is becoming increasingly difficult to use a single abrasive to meet these requirements. One way to solve the above problems is to composite abrasives, that is, the abrasive has two or more components at the same time. Since different types of abrasives in composite abrasives have different physical and chemical properties, the advantages of each abrasive can be fully utilized, thereby improving polishing efficiency and polishing effect. At the same time, after consulting relevant literature, there is currently little research on conformal polishing of nickel-phosphorus alloy microstructures, so it is urgent to carry out systematic conformal polishing research. Summary of the invention
[0007] The purpose of the present invention is to overcome the above-mentioned problems and provide a conformal polishing method for nickel-phosphorus grating microstructures with composite abrasives. The conformal polishing method combines abrasives of different hardnesses with polishing pads of different hardnesses to remove residual knife marks and reduce surface roughness while taking into account the shape of the microstructure to achieve conformal polishing.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A composite abrasive nickel-phosphorus grating microstructure conformal polishing method comprises the following steps:
[0010] (1) preparing a composite abrasive polishing liquid;
[0011] (2) Clean the workpiece surface and fix the workpiece on the polishing platform;
[0012] (3) Setting the spiral machining path, polishing load, and polishing time;
[0013] (4) preparing two polishing pads with different hardness, first using the polishing pad with higher hardness and the composite abrasive polishing liquid to polish the workpiece, and then using the polishing pad with lower hardness and the composite abrasive polishing liquid to polish the workpiece;
[0014] The composite abrasive polishing liquid produces slight oxidation corrosion on the surface of the nickel-phosphorus alloy workpiece, forming a chemically modified layer with weak bonding force; the composite abrasive polishing liquid includes two abrasives of different hardness, and the abrasive with higher hardness is driven by the polishing pad to move at a speed V and a load F, and the sharp part with higher hardness is used to remove the residual knife marks with larger fluctuations, that is, to eliminate the intermediate frequency error; after removing the intermediate frequency error, small and dense damage is introduced to form a high-frequency error; the abrasive with lower hardness is driven by the polishing pad to eliminate the high-frequency error, so that the intermediate and high frequency errors are removed at the same time, and the grating shape is taken into consideration to obtain a smooth surface;
[0015] During the macro-polishing process, pressure F is applied to the polishing pad, which is used to compress and deform the polishing pad while contacting the top and bottom of the grating microstructure. The polishing pad rotates at a speed ω and moves forward at a speed V, driving the composite abrasive to remove the chemically modified layer and achieve conformal polishing.
[0016] In a preferred embodiment of the present invention, the Mohs hardness of the abrasive with higher hardness is between 8.5 and 9.5, which is used to remove residual tool marks with larger fluctuations, i.e., medium-frequency errors; the Mohs hardness of the abrasive with lower hardness is between 6.5 and 7.5, which is used to remove small and dense damage, i.e., high-frequency errors.
[0017] In a preferred embodiment of the present invention, in step (1), the composite abrasive polishing liquid is prepared by:
[0018] Two abrasives of different hardness, dispersant propylene glycol, oxidant, and pure water are added in order and proportion, and stirred and vibrated to allow all ingredients to be completely dispersed and dissolved, and then the pH value is adjusted to the set value using a pH adjuster.
[0019] Furthermore, the abrasive with higher hardness is Al2O3, and its median particle size is 100nm to 1μm.
[0020] Furthermore, the percentage of Al2O3 is 0.15wt% to 0.3wt%.
[0021] Furthermore, the abrasive with lower hardness is SiO2, and its median particle size is 50nm.
[0022] Furthermore, the percentage of SiO2 is 1-2wt%.
[0023] Furthermore, the pH value is adjusted to be less than or equal to 3 by a pH adjuster.
[0024] Furthermore, the oxidant is H2O2, the mass percentage concentration thereof is 30%, and the content thereof is 0.8wt% to 1.2wt%.
[0025] In a preferred embodiment of the present invention, in step (4), the hardness of the polishing pad with higher hardness is 70 to 90 shoreA, and the hardness of the polishing pad with lower hardness is 40 to 60 shoreA.
[0026] In a preferred embodiment of the present invention, in step (4), the top corner of the grating microstructure is a stress concentration area, and the sharp corner becomes a rounded corner after polishing; limited by the material deformation limit of the polishing pad, the polishing pad drives the accumulated abrasive to remove a small amount of material from the bottom corner and side wall of the grating, so that after polishing, a chemically modified layer will remain on the bottom corner and side wall of the grating, and finally the bottom corner of the grating microstructure becomes a rounded corner;
[0027] The top of the grating microstructure contacts the polishing pad first, the material removal at the top of the grating is greater than that at the bottom of the grating, and the grating height H1 before polishing is greater than the grating height H2 after polishing, that is, the height of the grating will decrease after polishing.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The conformal polishing method of the present invention combines abrasives of different hardness with polishing pads of different hardness to remove residual knife marks and reduce surface roughness while taking into account the shape of the microstructure to achieve conformal polishing.
[0030] 2. The present invention is applicable to nickel-phosphorus alloy workpieces of various surface shapes and sizes, such as planes, aspheric surfaces, free-form surfaces, and can achieve conformal polishing of large-sized nickel-phosphorus grating microstructures. In addition to grating microstructures, the present invention is also applicable to conformal polishing of other optical microstructures, such as Fresnel microstructures.
[0031] 3. The present invention does not require specific conditions such as vacuum or magnetic field during polishing, is economical and practical, and can be applied to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the conformal polishing method of the nickel phosphorus grating microstructure of the present invention.
[0033] Figure 2 It is a cross-sectional schematic diagram of the grating before and after processing according to the nickel phosphorus grating microstructure conformal polishing method of the present invention.
[0034] Figure 3 The graph is a result of the nickel-phosphorus grating microstructure conformal polishing method of the present invention after polishing with different Al2O3 median particle sizes, where a is the surface morphology (detected by white light interferometer) and the power spectral density curve (PSD), b is the mean surface roughness; and c is the difference between the grating height and the widening change.
[0035] Figure 4This is a graph showing the results of the nickel-phosphorus grating microstructure conformal polishing method of the present invention after polishing with different Al2O3 contents, where a is the surface morphology (detected by white light interferometer) and the power spectral density curve (PSD), b is the mean surface roughness; and c is the difference between the grating height and the widening change.
[0036] Figure 5 The graphs are the result of polishing with different pH values using the conformal polishing method for nickel-phosphorus grating microstructures of the present invention, wherein a is the surface morphology (detected by white light interferometer) and the power spectral density curve (PSD), b is the mean value of the surface roughness; and c is the difference between the grating height and the widening change.
[0037] Figure 6 The graphs are result diagrams of the nickel-phosphorus grating microstructure conformal polishing method of the present invention after polishing with different H2O2 contents, wherein a is the surface morphology (detected by white light interferometer) and power spectral density curve (PSD), b is the surface morphology (detected by laser confocal microscope); c is the cross-sectional diagram of the corrosion pits of 1.4wt% and 2wt%; d is the mean value of the surface roughness; and e is the difference between the grating height and the widening change.
[0038] Figure 7 This is a schematic diagram of the nickel-phosphorus grating microstructure conformal polishing method of the present invention using polishing pads of different hardness for independent processing, wherein a is a schematic diagram of a hard polishing pad, and b is a schematic diagram of a soft polishing pad.
[0039] Figure 8 It is a schematic diagram of the nickel phosphorus grating microstructure conformal polishing method of the present invention using a combination of polishing pads with different hardness for processing.
[0040] Fig. 9 This is a result diagram of the nickel-phosphorus grating microstructure conformal polishing method of the present invention after processing using a combination of polishing pads with different hardnesses, in which a is the surface morphology (detected by white light interferometer); b is the mean surface roughness; c is the power spectral density curve (PSD); d is the grating height and width.
[0041] Fig.10 Schematic diagram of the calculation method of the conformal polishing effect measurement value ε. DETAILED DESCRIPTION
[0042] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0043] Example 1
[0044] See also Figure 1 The working principle of the conformal polishing method of nickel-phosphorus grating microstructure with composite abrasive of this embodiment is as follows:
[0045] During the movement of the polishing pad, the Al2O3 abrasive with high hardness, high removal rate and strong cutting force will be driven to move at a speed V and load F, and the sharp part of the Al2O3 surface will be used to remove the residual knife marks with large fluctuations, that is, the medium-frequency error. After the Al2O3 abrasive removes the medium-frequency error, it will introduce small and dense damage with fluctuations, that is, the high-frequency error. At this time, the polishing pad drives the spherical SiO2 with low hardness and low removal rate to remove the residual high-frequency error, and finally obtain a smooth surface. In the macro-polishing process, by applying pressure F to the polishing pad and utilizing the compression deformation of the polishing pad, the polishing pad can contact the top and bottom of the grating at the same time. At the same time, the polishing pad rotates at a speed ω and moves forward at a speed V, driving the SiO2 and Al2O3 composite abrasives to remove the chemically modified layer, thereby achieving polishing. Since the top corner of the grating belongs to the stress concentration area, the material removal rate is high, and the sharp corner will inevitably become a rounded corner after polishing. At the same time, due to the material deformation limit of the polishing pad, it is difficult to directly contact the bottom corner and side wall of the grating. The polishing pad drives the accumulated abrasive to remove a small amount of material from the bottom corner and side wall of the grating. Therefore, after polishing, a chemically modified layer will remain on the bottom corner and side wall of the grating, and the bottom corner of the grating will eventually become a rounded corner. In addition, since the top of the grating contacts the polishing pad first, the material removal of the top of the grating is greater than that of the bottom of the grating. The grating height H1 before polishing is greater than the grating height H2 after polishing, that is, the height of the grating will decrease after polishing. By adjusting the Al2O3 median particle size, Al2O3 content, pH value, oxidant content of the SiO2 and Al2O3 composite abrasive polishing liquid and the combined polishing of soft and hard polishing pads, the synergistic effect of the chemically modified layer formation rate and the mechanical removal of the abrasive can be controlled to achieve simultaneous removal of medium and high frequency errors, and the grating shape is taken into account to achieve conformal polishing.
[0046] See also Figure 2 In the present invention, the vertical distance between the top and bottom of the grating is defined as the height of the grating, and the horizontal distance between the top and bottom tangent fillets of the grating is defined as the width of the grating. The present invention uses the grating height and width as two indicators to measure the conformal effect.
[0047] Furthermore, the present invention mainly measures the conformal polishing of the nickel-phosphorus grating microstructure in two aspects. The first aspect is the polishing effect, which is mainly measured by the surface roughness value after polishing. The second aspect is the conformal effect, which is mainly measured by the difference between the grating height and the grating widening change after polishing. For the present invention, the polishing effect and the conformal effect are equally important. Therefore, the conformal polishing effect measurement value ε is defined as follows: Fig.10 .
[0048] It should be noted that, since the importance of the polishing effect and the conformal effect are the same, the proportion of the measurement value is 50% each, and in the conformal effect, the importance of the grating height and the grating widening is also the same, so the proportion of the measurement value is 25% each. The smaller the conformal polishing effect measurement value ε is, the better the conformal polishing effect is. The ideal value of the surface roughness of the present invention is set to RMS0.8nm, the ideal difference of the grating height decrease is 80nm, and the ideal difference of the grating widening increase is 12μm. For different actual application scenarios, the proportion of the conformal polishing measurement value and the ideal value can be set according to their own situation.
[0049] The conformal polishing method of the nickel-phosphorus grating microstructure using the composite abrasive of this embodiment comprises the following steps:
[0050] (1) Prepare a composite abrasive polishing liquid containing SiO2 and Al2O3. The specific operation is as follows:
[0051] SiO2 abrasive, Al2O3 abrasive, dispersant propylene glycol, oxidant and pure water were added in order and proportion, stirred with a magnetic stirrer for 15 minutes, and then ultrasonically vibrated with an ultrasonic cleaner for 15 minutes to completely disperse and dissolve the components, and then the pH was adjusted to an appropriate value with a pH adjuster.
[0052] Furthermore, the median particle size of the SiO2 is 50 nm.
[0053] Furthermore, the percentage of SiO2 should be 1-2wt%. This patent takes 1.5wt% as an example and conducts the following comparative experiments.
[0054] Furthermore, the median particle size of the Al2O3 is preferably 100 nm to 1 μm, specifically based on: see Table 1 and Figure 3When Al2O3 is 50nm, the median particle size is too small, the mechanical removal is weak, the abrasive is not able to remove the residual tool marks after turning, there are still many tool marks remaining after polishing, and the surface roughness decreases slightly after polishing. As the median particle size of Al2O3 increases to 100nm and 1μm, the mechanical removal of the abrasive is enhanced, the ability to remove the residual tool marks after turning increases, only a small amount of tool marks remain after polishing, and the surface roughness decreases to 1.2-1.3nm after polishing. As the median particle size of Al2O3 further increases to 5μm, the mechanical removal of the abrasive is too large, and the mechanical removal depth is much greater than the thickness of the chemically modified layer, which causes excessive scratching on the surface of the nickel-phosphorus grating microstructure, resulting in a large number of scratches, an increase in the surface roughness value, and a significant increase in the spatial frequency error of the power spectral density curve. Comparing the differences in grating height and broadening after polishing for different Al2O3 median particle sizes, the results show that as the Al2O3 median particle size increases, the damage to the grating after polishing gradually increases. This is because the increase in the Al2O3 median particle size leads to enhanced mechanical removal of abrasives, and the difference in material removal rates between the top and bottom of the grating further increases, causing the grating height to drop more after polishing. At the same time, the increase in the Al2O3 median particle size leads to enhanced mechanical removal, which further increases the material removal of the stress concentration area at the top corner of the grating, and the fillet formed at the top corner of the grating will be larger, that is, the grating broadening increases more after polishing. According to the calculation formula of the conformal polishing effect measurement value ε of the nickel-phosphorus grating microstructure (see below), the conformal polishing effect measurement values ε of four different Al2O3 median particle sizes after polishing are 0.48, 0.39, 0.36, and 5.67, respectively. Among them, the conformal polishing effect measurement values of the Al2O3 median particle sizes of 100nm and 1μm are close, indicating that the conformal polishing effects are close, so the Al2O3 median particle size can be selected between 100nm and 1μm. The present invention takes Al2O3 with a median particle size of 1μm as an example for subsequent optimization experiments.
[0055] Table 1 Process parameters of different Al2O3 median particle size comparison experiments
[0056]
[0057] Furthermore, the percentage of Al2O3 is preferably 0.15wt% to 0.3wt%, specifically based on:
[0058] See Table 2 and Figure 4When the Al2O3 content is 0.075wt%, the Al2O3 content is too low, and there are too few abrasives that can remove the residual tool marks. Therefore, the ability to remove the residual tool marks after turning is weak, the tool marks still exist obviously after polishing, and the average value of the surface roughness after polishing is still large. As the Al2O3 content increases to 0.15wt% and 0.3wt%, the content is moderate, and the ability to remove the residual tool marks after turning is enhanced. After polishing with 0.15wt% Al2O3, there is basically a small amount of residual tool marks, and after polishing with 0.3wt% Al2O3, the tool marks are completely removed, and the surface roughness can be reduced to about 1.2nm. Continue to increase the Al2O3 content to 0.75wt%, the surface roughness value is still large after polishing, and the power spectrum density curve rises overall after polishing. This is because the Al2O3 content is too high, and there are too many abrasives that can remove the residual knife marks, resulting in increased damage after polishing. Therefore, continue to increase the Al2O3 content. Although the knife marks can be completely removed, the surface roughness value is still large after polishing, and the power spectrum density curve rises overall after polishing. Comparing the difference in grating height and widening changes after polishing with different Al2O3 contents, from the results, with the increase of Al2O3 content, the overall damage to the grating after polishing gradually increases. This is because the increase of Al2O3 content with high removal rate will also enhance mechanical removal, and the difference in material removal rate between the top and bottom of the grating will increase. At the same time, the material removal rate in the stress concentration area of the top corner of the grating is further increased, and the fillet formed at the top corner of the grating will be larger, that is, the grating widening will increase more after polishing. Therefore, with the increase of Al2O3 content, the grating height and widening will change more after polishing. According to the calculation formula of the conformal polishing effect measurement value ε of the nickel-phosphorus grating microstructure, the conformal polishing effect measurement values ε after polishing of four different Al2O3 contents of 0.075wt%, 0.15wt%, 0.3wt%, and 0.75wt% are 0.49, 0.36, 0.35, and 5.67 respectively, among which the conformal polishing effect measurement values of 0.15wt% and 0.3wt% of Al2O3 content are close, indicating that the conformal polishing effects are close, so the Al2O3 content can be selected between 0.15wt% and 0.3wt%. The present invention takes 0.3wt% Al2O3 as an example for subsequent optimization experiments.
[0059] Table 2 Process parameters of the comparative experiment with different Al2O3 contents
[0060]
[0061] Further, the pH value is adjusted to less than or equal to 3 by a pH adjusting agent, specifically based on:
[0062] The pH value determines the most basic polishing processing environment and directly affects the surface quality after polishing. The most common acidic pH regulators are sulfuric acid and hydrochloric acid, and the alkaline pH regulators are sodium hydroxide and potassium hydroxide. These inorganic pH regulators are stable and not easy to decompose. Therefore, the present invention selects sulfuric acid as the acidic pH regulator and sodium hydroxide as the alkaline pH regulator to carry out the following process comparison test.
[0063] See Table 3 and Figure 5 When pH=3, 5, 7, and 9, the residual tool marks after turning can be basically completely removed after polishing, and the removal ability of residual tool marks is similar. When pH=11, the removal ability of residual tool marks after turning decreases, and the residual tool marks after polishing still exist obviously. This is because in the polishing liquid, the nickel-phosphorus alloy will be oxidized and corroded into nickel and phosphorus oxides, and the phosphorus oxide will be hydrolyzed. At the same time, the nickel oxide will react with water to form nickel hydroxide. Nickel hydroxide has a weak ionization equilibrium in water. In acidic conditions, H + It can react with hydroxides to promote the reaction to the right, thereby accelerating the formation of the chemically modified layer and achieving the dissolution of the polishing product. When pH = 11, OH - When the concentration is too high, the formation of the chemically modified layer is slowed down, the material removal rate decreases, and the residual knife marks are removed slowly. The average surface roughness after polishing at different pH values is around RMS1~1.3nm, and the ability to reduce surface roughness is similar. Comparing the difference in the change of grating height and width after polishing at different pH values, from the results, when pH=3 and 11, the change in the grating height and width after polishing is relatively small. This is because when the Al2O3 abrasive is at pH=7, the surface charge is 0, that is, the isoelectric point. The pH near the isoelectric point is prone to be in an unstable state, the attraction between the abrasives is greater than the repulsion between the double electric layers, and it is easy to agglomerate during polishing [5]. Therefore, at pH=5, 7, and 9, the abrasive agglomeration leads to increased mechanical removal and severe damage to the grating shape after polishing. The calculation formula for the measure value ε of the conformal polishing effect of nickel-phosphorus grating microstructure is as follows. The measure values of the conformal polishing effect after polishing at five different pH values of 3, 5, 7, 9, and 11 are 0.07, 0.36, 0.35, 0.40, and 0.13, respectively. Therefore, the pH value should be adjusted to less than or equal to 3, which is more conducive to removing residual tool marks, reducing surface roughness, taking into account the grating shape, and achieving conformal polishing.
[0064] Table 3 Process parameters of different pH value comparison experiments
[0065]
[0066]
[0067] Furthermore, the oxidant is H2O2, and its mass percentage concentration is 30%, and its content is preferably 0.8wt% to 1.2wt%, specifically based on:
[0068] Oxidant is an important component in chemical mechanical polishing. Its main function is to oxidize and corrode the surface material into a chemically modified layer. By studying the influence of oxidant concentration, the surface quality after polishing can be controlled. Commonly used oxidants include potassium sulfate, potassium ferrate, potassium permanganate, hydrogen peroxide, etc. Among them, hydrogen peroxide has a strong oxidation ability and does not pollute the polishing liquid with impurity ions. The generated oxidation product is water. Therefore, the present invention selects 30% H2O2 as the oxidant for polishing and carries out the following process comparison test.
[0069] See Table 4 and Figure 6 When the H2O2 content is 0.2wt% and 0.6wt%, the oxidation corrosion is weak, and the chemical modification layer is formed slowly, resulting in slow removal of residual knife marks. After polishing, there are still wide residual knife marks, and the surface roughness after polishing is still large. When the H2O2 content is greater than or equal to 1.4wt%, the oxidant content is too high, the oxidation corrosion is too strong, and the oxidant will corrode downward along the micro-damage on the surface, eventually forming corrosion pits, resulting in a significant increase in the spatial frequency error of the power spectrum density curve, and the surface roughness deteriorates and increases. With the increase of the oxidant concentration, the corrosion pits deepen; when the H2O2 content is 1wt%, the oxidant content is appropriate, the residual knife marks can be completely removed after polishing, no corrosion pits appear, and the surface roughness drops to about 1nm. Comparing the difference between the grating height and the widening change after polishing with different oxidant contents, the results show that the widening change value of the grating decreases when the oxidant content is too high. This is because the excessive oxidant content causes excessive oxidation of the material surface, forming an overly thick oxide layer, which in turn weakens the mechanical removal of the stress concentration area at the top corner of the grating, indirectly protecting the grating. The fillet formed at the top corner of the grating is smaller, that is, the grating widening changes less after polishing. The formula for calculating the conformal polishing effect measurement value ε of the nickel-phosphorus grating microstructure is 0.51, 0.38, 0.07, 1.76, and 1.65 after polishing with five different H2O2 contents of 0.2wt%, 0.6wt%, 1wt%, 1.4wt%, and 2wt%, respectively. When the H2O2 content is 0.6wt%, there are residual knife marks, when it is 1.4wt%, there are corrosion pits, and when it is 1wt%, the effect is the best. Considering that the optimal content value fluctuates within a certain range, the H2O2 content should be selected between 0.8wt% and 1.2wt%. The present invention takes 1wt% H2O2 as an example for subsequent optimization experiments.
[0070] Table 4 Process parameters of the comparative experiment with different oxidant contents
[0071]
[0072] (2) After cleaning the surface of the workpiece with anhydrous ethanol and pure water, fix the workpiece on the polishing platform.
[0073] (3) Set the spiral machining path with a pitch of 1 mm and a speed of 0.42 N / cm 2 Polishing load; It should be noted that, in the actual processing process, the pitch of the spiral path can be adjusted according to the size of the processing sample and the size of the polishing disk.
[0074] (4) First, use a polishing pad with a hardness of 70 to 90 shoreA and the composite abrasive polishing liquid to polish the workpiece for 2 hours, and then use a polishing pad with a hardness of 40 to 60 shoreA and the composite abrasive polishing liquid to polish the workpiece for 1 hour. (It should be noted that the sample polished in this patent is a circular plane sample with a diameter of 100 mm. For samples of other sizes, refer to this patent and reasonably calculate the polishing time based on the area ratio)
[0075] Considering that the workpiece processed by the present invention has a grating microstructure, a polishing pad that is too hard will cause the grating bottom to be unable to be polished, and a polishing pad that is too soft will cause the polishing pad to wear too quickly and be unable to effectively remove the surface material, resulting in a decrease in polishing efficiency. Figure 7 Therefore, the hardness of the hard polishing pad should be controlled within the Shore A hardness range of 70 to 90, and the hardness of the soft polishing pad should be controlled within the Shore A hardness range of 40 to 60.
[0076] Example 2
[0077] See Table 5 and Figures 8-9 The Shore hardness of the non-woven polishing pad used in this embodiment is Shore A80, and the Shore hardness of the damping cloth polishing pad is Shore A52. The texture of the non-woven fabric is relatively harder.
[0078] After 2 hours of polishing with non-woven fabric, the residual knife marks after turning were completely removed, and the surface roughness was about RMS 1nm. On this basis, polishing with damping cloth for 1 hour can effectively reduce the surface roughness to RMS0.8nm. The power spectral density curve (PSD) shows that after polishing with damping cloth for 1 hour, the surface roughness can be further reduced by 10 1 ~10 3 mm ~1 The spatial frequency error of the two polishing pads is 0.13. The grating height is reduced by 84nm and the width is increased by 12.98μm. The conformal polishing effect measurement value ε of the nickel-phosphorus grating microstructure is calculated by the formula. The conformal polishing effect measurement value ε of the two polishing pads with different hardness is 0.13.
[0079] Table 5 Process parameters of polishing with different polishing pad combinations
[0080]
[0081] The above is a preferred embodiment of the present invention, but the embodiment of the present invention is not limited to the above content. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for conformal polishing of nickel-phosphorus grating microstructures using composite abrasives, characterized in that: The following steps are involved: (1) preparing a composite abrasive polishing liquid; (2) Clean the workpiece surface and fix the workpiece on the polishing platform; (3) Setting the spiral machining path, polishing load, and polishing time; (4) preparing two polishing pads with different hardness, first using the polishing pad with higher hardness and the composite abrasive polishing liquid to polish the workpiece, and then using the polishing pad with lower hardness and the composite abrasive polishing liquid to polish the workpiece; The composite abrasive polishing liquid generates oxidation corrosion on the surface of the nickel-phosphorus alloy workpiece to form a chemically modified layer; the composite abrasive polishing liquid includes two abrasives of different hardness, and the abrasive with higher hardness is driven by the polishing pad to move at a speed V and a load F, and the sharp part of the abrasive with higher hardness is used to remove the residual knife marks, that is, to eliminate the intermediate frequency error; after removing the intermediate frequency error, damage is introduced, and the fluctuation difference of the damage is smaller than the fluctuation difference of the residual knife marks, forming a high-frequency error; the abrasive with lower hardness is driven by the polishing pad to eliminate the high-frequency error, so that the intermediate and high frequency errors are removed at the same time, and the grating shape is taken into consideration to obtain a smooth surface; During the macro-polishing process, pressure F is applied to the polishing pad, which is used to compress and deform the polishing pad while contacting the top and bottom of the grating microstructure. The polishing pad rotates at a speed ω and moves forward at a speed V, driving the composite abrasive to remove the chemically modified layer and achieve conformal polishing.
2. The method for conformal polishing of nickel-phosphorus grating microstructures using composite abrasives according to claim 1, characterized in that: The Mohs hardness of abrasives with higher hardness is between 8.5 and 9.5, and is used to remove residual tool marks, that is, medium-frequency errors; the Mohs hardness of abrasives with lower hardness is between 6.5 and 7.5, and is used to remove introduced damage, that is, high-frequency errors.
3. The method for conformal polishing of nickel-phosphorus grating microstructures using composite abrasives according to claim 2, characterized in that: In step (1), the composite abrasive polishing liquid is prepared by: Two abrasives of different hardness, dispersant, oxidant and pure water are added in order and proportion, and stirred and vibrated to make all the ingredients completely dispersed and dissolved, and then the pH value is adjusted to the set value by the pH adjuster.
4. The method for conformal polishing of nickel-phosphorus grating microstructures using composite abrasives according to claim 3, characterized in that: The abrasive with higher hardness is Al2O3, and its average particle size is 100nm-1μm.
5. The method for conformal polishing of nickel-phosphorus grating microstructure with composite abrasive according to claim 3, characterized in that: The percentage of Al2O3 is 0.15wt% to 0.3wt%.
6. The method for conformal polishing of nickel-phosphorus grating microstructure with composite abrasive according to claim 3, characterized in that: The abrasive with lower hardness is SiO2, wherein the median particle size is 50nm; the percentage of SiO2 is 1-2wt%.
7. The method for conformal polishing of nickel-phosphorus grating microstructures with composite abrasives according to claim 3, characterized in that: The pH value is adjusted to less than or equal to 3 by a pH adjuster.
8. The method for conformal polishing of nickel-phosphorus grating microstructures with composite abrasives according to claim 3, characterized in that: The oxidant is H2O2, the mass percentage concentration thereof is 30%, and the content thereof is 0.8wt% to 1.2wt%.
9. The method for conformal polishing of nickel-phosphorus grating microstructures with composite abrasives according to claim 1, characterized in that: In step (4), the hardness of the polishing pad with higher hardness is 70 to 90 shoreA, and the hardness of the polishing pad with lower hardness is 40 to 60 shoreA.
10. The method for conformal polishing of nickel-phosphorus grating microstructures with composite abrasives according to claim 1, characterized in that: In step (4), the top corner of the grating microstructure is a stress concentration area, and the sharp corner becomes a rounded corner after polishing; limited by the material deformation limit of the polishing pad, the polishing pad drives the accumulated abrasive to remove a small amount of material from the bottom corner and side wall of the grating, so that after polishing, a chemically modified layer will remain on the bottom corner and side wall of the grating, and finally the bottom corner of the grating microstructure becomes a rounded corner; The top of the grating microstructure contacts the polishing pad first, the material removal at the top of the grating is greater than that at the bottom of the grating, and the grating height H1 before polishing is greater than the grating height H2 after polishing, that is, the height of the grating will decrease after polishing.
Citation Information
Patent Citations
Polishing solution and polishing method of cadmium zinc telluride material
CN107384218A
Greenness and environmental-protection chemico-mechanical polishing method for nickel alloys
CN109848821A
Application of composite abrasive polishing solution in polishing product and polishing method
CN117777861A
Magnetic float polishing processes and materials therefor
WO1999016577A2
Cited By
Magneto-rheological polishing polyhedral integrated element integrated machining method
CN121315771A
Method for magnetorheological finishing of multi-faceted conformal element
CN121315771B